Comparison between Techniques of Computational Modeling of Wall-Type Buildings - Álvarez González, Sergio Gabriel (2025)
This paper compares the application of different computational modeling techniques of wall-type buildings; specifically, the following modeling methodologies were studied: Modeling through frame type elements with rectangular cross-section Modeling through frame type elements with irregular cross-section Modeling through shell type elements In order to apply each modeling techniques to different buildings, the structural analysis software called ETABS was used. In which a spectral dynamic analysis of each one of these models was carried out, with which a results matrix was created that allowed comparing and discussing the different global structural responses that can be obtained for the same building when a linear analysis is carried out using different modeling techniques. From this comparison, it is concluded that in general, the models composed of frame type elements with a rectangular cross-section and the models made with area type elements show similar behaviors, so that wall-type buildings of up to 30 levels could be modeled with both methodologies without significant differences in structural responses (periods, seismic forces at the base of the structure and drifts). On the other hand, models made with frame type elements with irregular cross-section presented significant differences for these same responses.